2022
DOI: 10.3390/polym14214486
|View full text |Cite
|
Sign up to set email alerts
|

Polybutylene Succinate Processing and Evaluation as a Micro Fibrous Graft for Tissue Engineering Applications

Abstract: A microfibrous tubular scaffold has been designed and fabricated by electrospinning using poly (1,4-butylene succinate) as biocompatible and biodegradable material. The scaffold morphology was optimized as a small diameter and micro-porous conduit, able to foster cell integration, adhesion, and growth while avoiding cell infiltration through the graft’s wall. Scaffold morphology and mechanical properties were explored and compared to those of native conduits. Scaffolds were then seeded with adult normal human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The optimized scaffold morphology featured a small diameter and micro-porous conduit, facilitating cell integration, adhesion, and growth while preventing cell infiltration through the graft’s wall. Mechanical properties of the tubular conduits fell within the physiological range as well [ 17 ]. Additionally, Vigni et al demonstrated in another study that a PBS microfibrillar scaffold used in critical bone defects on a rabbit model could potentially enhance bone regeneration [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optimized scaffold morphology featured a small diameter and micro-porous conduit, facilitating cell integration, adhesion, and growth while preventing cell infiltration through the graft’s wall. Mechanical properties of the tubular conduits fell within the physiological range as well [ 17 ]. Additionally, Vigni et al demonstrated in another study that a PBS microfibrillar scaffold used in critical bone defects on a rabbit model could potentially enhance bone regeneration [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polybutylene succinate (PBS) scaffold has proven to be an excellent biomaterial in various fields, including osteogenesis [ 10 ], with high biocompatibility and easy processability by electrospinning technique [ 11 , 12 ]. It is a commercially available, biodegradable, thermoplastic aliphatic polyester synthesized by the polycondensation of succinic acid and butanediol.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric nanofibrillar scaffolds, due to their suitable physicochemical and morphological properties, represent excellent platforms for tissue engineering and biomedical applications [ 24 , 25 , 26 ]. The microstructure of such systems is comparable to the tissues extracellular matrix (ECM) and it is crucial for adhesion, growth, and cell proliferation [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%